Patient safety climate in medical and surgical units - Maria Helena Barbosa; Thuanne Cristina Sousa e Aleixo; Karoline Faria de Oliveira; Kleiton Gonçalves do Nascimento; Márcia Marques dos Santos Felix; Elizabeth Barichello (Universidade Federal de Goias, 2016)
Cross-sectional, analytical and quantitative study with the objective of evaluating the patient safety climate from the perspective of nursing staff professionals in medical and surgical units. Fifty-two professionals participated. Data were collected using the Safety Attitudes Questionnaire. The Student's t-test and Spearman's correlation coefficient (α = 0.05) were used for analyses. The mean overall score for the instrument was 66.94 points. The factor with the best score was Perceptions of Management (84.60), and the ones with the lowest scores were Working Conditions (60.15) and Stress Recognition (55.59). There were statistically significant differences between genders and educational levels for the safety climate factor. There were no relationships for professional performance, employment bonds or professional categories. Weaknesses in staff's safety climate perception were observed, which point to the need to institute strategies to promote a safe climate.